Kepuasan Kerja dalam Perusahaan Distributor Rokok - Dewi Wungkus Antasari (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
This research aim to know the work mecanism of the marketing coorporate with a lot of pressures the worker got. Also to know what factors can affect worker to get their job satisfication. This research use qualitative method with the case-study approach because the researcher will know directly about the work mecanism, worker’s opinion about coorporate facilities, leadership style, workload, coworkers, and also the salary they got. The result of the research will prove that coorporate is truly make worker’s satisfication and also affect towards worker’s organizational commitment.